Analisis Potensi dan Problematika Desa Tertinggal di Kabupaten Konawe Selatan - Peribadi Peribadi (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2023)
The presence of rural areas along with their potential and issues appears distinctly different among the statuses of Self-Reliant Villages, Progressive Village, Developing Village, and Underdeveloped Village. This research is aimed at examining and depicting the existence of Underdeveloped Villages, along with all their potential and the societal issues experienced daily. The study employs a quantitative descriptive approach, coupled with an analysis of the Village Development Index (VDI), to comprehensively identify supporting and inhibiting potentials, such as opportunities and challenges. The research results indicate that the potentials and issues of Tambeanga Village in Laonti Subdistrict, South Konawe Regency, as outlined in the context of social resilience with 38 indicators, economic resilience with 12 indicators, and ecological resilience with four indicators, as stated in the instrument of the Ministry of Villages, Disadvantaged Regions, and Transmigration of the Republic of Indonesia Number 2 of 2016, show the level of being an underdeveloped village, approaching even the status of a severely underdeveloped villages. Various factors contribute to its underdevelopment and backwardness, preventing the optimal utilization of natural resources to build the area and improve its socio-economic well-being.